Submicron plate-shaped tin phosphide lithium and sodium storage material and battery
Solvent Thermal method is used to synthesize and sublimate the treatment of tin phosphide, and sub-micrometer plate-like tin phosphide nanosheets are prepared, combining acetylene black and sodium alginate, which solves the problems of complex preparation of tin phosphide and insufficient electrochemical performance in the prior art. , achieves high capacity and cycle stability of lithium-ion and sodium-ion battery negative electrode materials.
Patent Information
- Application Number
- CN202411056489.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-02
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-08-02
AI Technical Summary
The existing preparation methods for tin phosphide are complex and time-consuming. The need for excessive red phosphorus during synthesis of solvent thermal methods leads to limited battery capacity and life, and the material size and structure are difficult to control, affecting electrochemical performance.
Solvent-thermal method is used to synthesize tin phosphide, by mixing the soluble tin-based material with red phosphorus and polar amine solution and sublimating excess red phosphorus in an inert atmosphere, obtaining submicron plate-like tin phosphide nanosheets and with acetylene Black and sodium alginate are combined for lithium-ion or sodium ion battery negative electrode materials.
It realizes high reversibility of lithium storage and sodium storage, improves the cycle stability and capacity of lithium-ion and sodium-ion batteries, simplifies the process, reduces costs, and is suitable for large-scale production.
Smart Images

Figure CN119133438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of battery electrode materials, and in particular to a submicron plate-shaped tin phosphide lithium and sodium storage material and a battery. Background Art
[0002] Tin phosphide with submicron plate structure is very ideal for advanced electronic, magnetic, optoelectronic and sensing applications. The performance of particles depends largely on their phase, size, shape and dimensions. It is very important to develop scalable and simple routes to produce syntheses with controlled size and microstructure. For lithium-ion batteries, tin phosphide provides a capacity of nearly 1130mAh / g, which is much higher than the 372mAh / g of traditional graphite anode materials. The mechanism behind this high capacity is that the structure of tin phosphide allows lithium ions to be embedded and released in multiple stages inside it, thus providing excellent capacity and charge and discharge stability.
[0003] The main preparation methods of tin phosphide include ball milling, calcination, hydrothermal and solvothermal methods, each of which has its own unique advantages and limitations. The ball milling method relies on the strong mechanical force of a high-energy ball mill to achieve powder mixing and particle size reduction. This method has extremely high equipment requirements and has certain challenges in terms of crystallinity. The calcination method achieves phosphation by exposing the precursor to phosphine gas, which can produce high-purity tin phosphide. However, the high toxicity of phosphine and the need for precise control of the precursor limit its wide application. In addition, the difficult-to-control particle size and structure during the calcination process may cause the prepared tin phosphide to exhibit poor cycle stability and limited battery life. The hydrothermal method allows synthesis at lower temperatures, which helps to maintain the structural integrity of the material. However, the synthesis steps of this method are cumbersome and the reproducibility is poor, which limits its application in large-scale production. Qian et al. synthesized Sn by ball milling using elemental tin, red phosphorus and 30% carbon black as raw materials. 4 P 3 / C negative electrode material as lithium storage material, at 100mA g -1 After 150 cycles of charge and discharge at a current density of 500 mAh g -1 However, the particle size of this material is large and cannot achieve ideal electrochemical performance (ACS Nano 2020, 14, 8826-8837); for example, Li et al. used tin dichloride, sodium borohydride and PVP as raw materials to synthesize Sn by low-temperature solution chemistry 4 P 3 / RGO composites, as sodium storage materials, at 100mA g -1 After 100 cycles of charge and discharge at a current density of , the capacity is 656 mAh g -1The material has a high capacity, but the low coulombic efficiency reduces the overall electrochemical performance of the material (Adv. Energy Mater. 2016, 6, 1600376-1600386). For example, Qing et al. synthesized Sn using tin dichloride, red phosphorus and carbon nanotubes as raw materials by a one-step solvothermal method. 4 P 3 / CNT materials, as LIB negative electrode materials, at 500mA g -1 After 300 cycles of charge and discharge at a current density of , the capacity is 976.5 mAh g -1 However, the particle size of this material is large and cannot achieve ideal electrochemical performance (ChemElectroChem2018, 15, 2150-2156).
[0004] The invention patent with patent number CN110993913A discloses that tin tetrachloride is used as raw material, sodium hypophosphite is used as phosphorus source, and expanded graphite prepared by chemical oxidation is used as conductive agent, and the mixture is added into a ball mill for wet ball milling synthesis to obtain a tin phosphide / expanded graphite negative electrode sodium storage material with a particle size of 80 to 200 nm and a carbon content of 16.7 wt%. The tin phosphide synthesized by this method has a smaller particle size than the conventionally synthesized tin phosphide. At the same time, the graphite sheet peeled from the expanded graphite is successfully coated with tin phosphide to form a spherical composite material. The thickness of the coating layer is about 5 to 6 nm, and the spherical composite material is loaded on the peeled graphite sheet to form a conductive network. As a SIB negative electrode material, after 100 cycles of constant current charge and discharge at 500 mA / g, the specific capacity can still be maintained at 409 mAh / g, showing good cycle stability.
[0005] The invention patent with patent number CN111082034A discloses a preparation method using sodium alginate as raw material, cross-linking with tetravalent tin ions, carbonization and then phosphating to obtain a tin / tin phosphide / carbon composite material. When applied to the negative electrode of a lithium-ion battery, at a current density of 0.1A / g, the first coulomb efficiency is 50%, and the capacity is still 665mAh / g after 100 cycles; the cycle performance at a current density of 1A / g is 1767mAh / g for the first discharge ratio of smelting, and continues to rise after a period of capacity decay, with a specific capacity of up to 920mAh / g at 500 cycles, showing good cycle performance and rate performance.
[0006] In summary, the methods for preparing tin phosphide reported in existing literature are complex and time-consuming to prepare, and the existing literature and actual operation of the solvothermal synthesis of tin phosphide show that an excessive amount of red phosphorus must be added to successfully synthesize tin phosphide. Due to the low conductivity and high expansion of red phosphorus itself, it has a huge negative impact on battery capacity and life. Composite carbon is needed to overcome these shortcomings of red phosphorus, so it has the limitation of composite carbon. Synthesizing composite carbon with controlled morphology, size, chemical composition and getting rid of the solvothermal synthesis of tin phosphide is an important step towards the industrial popularization and application of the solvothermal synthesis of tin phosphide. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a submicron plate-shaped tin phosphide lithium and sodium storage material and a battery.
[0008] The technical solution adopted by the present invention is as follows: The first aspect of the present invention is to provide a submicron plate-shaped tin phosphide lithium storage sodium storage material, and the preparation method thereof comprises the following steps:
[0009] S1: taking a soluble tin-based material, red phosphorus, and a polar amine solution, placing them in a reaction container, mixing and heating them, centrifuging, washing, and drying them to obtain tin phosphide and excess red phosphorus;
[0010] S2: The tin phosphide obtained in step S1 and excess red phosphorus are placed in an inert atmosphere and heated to sublime the excess red phosphorus to obtain submicron flaky tin phosphide.
[0011] Preferably, in step S1, the molar ratio of the soluble tin-based material to red phosphorus is 1:160-200.
[0012] Preferably, the soluble tin-based material is tin and / or stannous chloride.
[0013] Preferably, the polar amine solution is ethanolamine and / or ethylenediamine.
[0014] Preferably, step S1 specifically includes the following steps:
[0015] S1.1: Soluble tin-based materials and red phosphorus are added to the inner lining of a reactor, and then a polar amine solution is added;
[0016] S1.2: Place the reactor liner in an oil bath, heat and stir;
[0017] S1.3: After stirring, immediately put the reactor liner into the high-temperature reactor, and place the high-temperature reactor in a preheated oven to heat and keep warm;
[0018] S1.4: Centrifuge, wash and dry the solution obtained in step S1.3 to obtain tin phosphide and excess red phosphorus.
[0019] Preferably, in step S1.2, the heating temperature is 80-100° C. and the heating time is 30-60 minutes.
[0020] Preferably, in step S1.3, the heating temperature is 180°C-220°C, and the temperature holding time is 10-24h.
[0021] Preferably, in step S2, the inert gas is nitrogen or argon, the sublimation temperature is 370-420° C., and the sublimation time is 1-40 h.
[0022] The second aspect of the present invention is to provide a battery, which is a lithium ion battery or a sodium ion battery, which uses the submicron plate-like tin phosphide lithium and sodium storage material as described above as the negative electrode material.
[0023] Preferably, the preparation method comprises the following steps:
[0024] (A) weighing submicron plate-shaped tin phosphide lithium storage sodium storage material, acetylene black and sodium alginate, adding a certain amount of distilled water, mixing evenly, grinding and stirring into a paste, and applying it on a copper foil;
[0025] (B) Drying, slicing, assembling and pressing the coated copper foil to obtain the lithium ion battery or sodium ion battery.
[0026] The beneficial effects of the present invention are as follows:
[0027] The present invention prepares a solvent-thermal chemical route containing excess red phosphorus and Sn 4 P 3 The product is then removed by sublimation to obtain submicron plate-like tin phosphide nanosheets. The synthesized product is characterized in detail by electrochemical performance, which is excellent in LIBs negative electrode and has high sodium / lithium storage reversibility. The thinner submicron sheet shortens the Na + / e - and Li + / e - The transfer distance is shortened, and the kinetics of lithium and sodium storage reactions are increased, thereby achieving excellent cycle stability. This method provides higher capacity and better cycle stability for lithium-ion batteries and sodium-ion batteries. Compared with existing reports, the preparation method of the present invention is simple in process, low in cost, and easier to mass produce. The obtained submicron plate-shaped tin phosphide has excellent cycle performance and rate performance in lithium-ion batteries and sodium-ion batteries.
[0028] The submicron plate-shaped tin phosphide material prepared in one embodiment of the present invention is used as a negative electrode for LIB. After 100 cycles at a current density of 100mA / g, the lithium storage capacity can reach 662mAh / g, and the capacity gradually increases with the number of cycles. After 100 cycles, the capacity is stable at about 1720mAh / g. As a negative electrode for SIB, the submicron plate-shaped tin phosphide material can maintain a capacity of up to 310mA / g when the sample is cycled for 60 cycles at a current of 50mA / g, and the performance is significantly higher than the results of published articles in the prior art. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.
[0030] Figure 1 The scanning electron microscope (SEM) images (de) of the submicron plate-like tin phosphide after sublimation prepared in Example 1; the scanning electron microscope (SEM) images (ac) of the tin phosphide before sublimation prepared in Comparative Example 1;
[0031] Figure 2 The X-ray diffraction (XRD) patterns of the submicron plate-like tin phosphide after sublimation prepared in Example 1 and the tin phosphide before sublimation prepared in Comparative Example 1 (b, a);
[0032] Figure 3 The sublimated submicron plate-shaped tin phosphide material prepared in Example 1 is used as the negative electrode of a lithium ion battery at 100 mA g -1 , Cyclic stability test diagrams at different current densities (ad);
[0033] Figure 4 The sublimated submicron plate-shaped tin phosphide material prepared in Example 1 is used as the negative electrode of a sodium ion battery at 20 mA g -1 , 50mA g -1 , 200mA g -1 , 500mA g -1 , 1000mA g -1 , Cyclic stability test diagrams at different current densities (ad); DETAILED DESCRIPTION
[0034] In order to make the objectives, technical solutions and advantages of the present invention more clear, the present invention will be further described in detail below with reference to the accompanying drawings.
[0035] Embodiment 1:
[0036] A method for preparing a submicron plate-shaped tin phosphide lithium and sodium storage material, comprising the following steps:
[0037] S1: Take 0.4 g of stannous chloride dihydrate (SnCl 2 ·2H 2 O) and 1.2 g of red phosphorus (P) were added to the polytetrafluoroethylene lining of the reactor. Subsequently, 20 ml of ethanolamine solution was injected.
[0038] S2: Place the reactor liner and the solution in an oil bath, add a magnet, adjust the temperature to 90°C, and maintain this temperature with stirring for 60 minutes.
[0039] S3: After stirring, immediately put the reactor liner into the stainless steel high-temperature reactor. After ensuring that the reactor is tightened, place it in a preheated oven, set the temperature to 180°C, and keep it under this condition for 15 hours.
[0040] S4: centrifuging the solution obtained in step S3 to obtain a solid product, washing the solid product with water and ethanol, and drying to obtain a tin phosphide product and excess red phosphorus.
[0041] S5: The product obtained in step S4 is placed in an inert atmosphere and heated to sublime the red phosphorus to obtain submicron flaky tin phosphide.
[0042] S6: Submicron flaky tin phosphide material, acetylene black and sodium alginate are mixed evenly in a mass ratio of 8:1:1, and an appropriate amount of ultrapure water is added. The mixture is stirred continuously into a paste and applied onto copper foil. The coated copper foil is dried, pressed into sheets and the battery is assembled.
[0043] Comparative Example 1:
[0044] The preparation process of this comparative example is substantially the same as that of Example 1, with the only difference being that there is no step S5.
[0045] Microscopic characterization
[0046] The tin phosphide materials obtained in Example 1 and Comparative Example 1 were subjected to microscopic characterization by different means:
[0047] Figure 1 The SEM images (cd) of the submicron plate-like tin phosphide in Example 1 and the SEM images (ac) of the non-sublimated red phosphorus in Comparative Example 1 are shown. It can be seen from the SEM that the thickness of the submicron plate-like tin phosphide synthesized in Example 1 is about 1 μm or less, and the morphology is irregular flake, large-scale, thin and uniformly distributed; the non-sublimated red phosphorus in Comparative Example 1 is a block of tens of microns.
[0048] Figure 2The XRD diagram of submicron plate-like tin phosphide in Example 1 (b) and the XRD diagram of non-sublimated red phosphorus in Comparative Example 1 (a); it can be seen that the sublimation process of red phosphorus will affect Sn 4 P 3 Produces a little phase change effect.
[0049] Electrochemical performance characterization
[0050] Figure 3 The submicron plate-shaped tin phosphide in Example 1 and the non-sublimated red phosphorus in Comparative Example 1 are used as the negative electrode of a lithium ion battery at 100 mA g -1 Figure (a) and different rate graphs (b) of the cycling stability test under current density; Submicron plate-like tin phosphide at 1000mA g -1 Cyclic stability test under current density (d) and 100mA g -1 The charge and discharge curves under current density (c). By comparing the cycle stability performance graph, it can be seen that the submicron plate-like tin phosphide lithium storage negative electrode material of Example 1 is 100mA g -1 At this current density, the capacity is still 662 mAh g after 100 cycles. -1 ; and the capacity gradually increases with the number of cycles, reaching 1723mA g after 1000 cycles -1 , showing good life and capacity; at different rates, the current density returned to 100mA g after 60 cycles -1 In this case, the capacity can be better returned to 677mAh g -1 ; and at 100, 200, 500 and 1000, 2000mA g -1 After 120 cycles at high current density, the capacities were maintained at 757, 665, 591, 543 and 494 mAh g -1 Comparative Example 1: The capacity of the non-sublimated red phosphorus lithium storage negative electrode material does not exceed 50 mAh g after 5 cycles at various rates. -1 . It shows that submicron plate-like tin phosphide high-performance lithium and sodium storage materials have high lithium storage reversibility when used as negative electrodes for lithium-ion batteries.
[0051] Figure 4 The submicron plate-shaped tin phosphide in Example 1 and the non-sublimated red phosphorus in Comparative Example 1 are used as the negative electrode of the sodium ion battery at 20 mA g -1 Figure (a), 50mA g -1 Figure (b) and different rate graphs (c) are cycle stability test graphs at current densities; in Example 1, submicron plate-shaped tin phosphide was subjected to 100 mA g -1The charge and discharge curves under current density (d) show that the submicron plate-like tin phosphide sodium storage negative electrode material synthesized by surfactant adsorption in Example 1 is 50 mA g -1 At this current density, the capacity is still 310 mAh g after 60 cycles. -1 ; at 500mA g -1 At the current density, the capacity is 209 mAh g after 60 cycles. -1 ; Under different rates, the current density returned to 20 mA g after 60 cycles -1 In this case, the capacity can return to 670mAh g -1 ; Comparative Example 1 The capacity of the non-sublimated red phosphorus lithium storage negative electrode material does not exceed 50 mAh g after 5 cycles at each rate -1 . It shows that submicron plate-like tin phosphide high-performance lithium and sodium storage materials have high sodium storage reversibility when used as negative electrodes for sodium-ion batteries.
[0052] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.
Claims
1. A submicron plate-like tin phosphide lithium and sodium storage material, characterized in that: The preparation method thereof comprises the following steps: S1: taking a soluble tin-based material, red phosphorus, and a polar amine solution, placing them in a reaction container, mixing and heating them, centrifuging, washing, and drying them to obtain tin phosphide and excess red phosphorus; S2: The tin phosphide obtained in step S1 and excess red phosphorus are placed in an inert atmosphere and heated to sublime the excess red phosphorus to obtain submicron flaky tin phosphide.
2. A submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 1, characterized in that: In step S1, the molar ratio of the soluble tin-based material to red phosphorus is 1:160-200.
3. A submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 1, characterized in that: The soluble tin-based material is tin and / or stannous chloride.
4. A submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 1, characterized in that: The polar amine solution is ethanolamine and / or ethylenediamine.
5. The submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 1, characterized in that: Step S1 specifically includes the following steps: S1.1: Soluble tin-based materials and red phosphorus are added to the inner lining of a reactor, and then a polar amine solution is added; S1.2: Place the reactor liner in an oil bath, heat and stir; S1.3: After stirring, immediately put the reactor liner into the high-temperature reactor, and place the high-temperature reactor in a preheated oven to heat and keep warm; S1.4: Centrifuge, wash and dry the solution obtained in step S1.3 to obtain tin phosphide and excess red phosphorus.
6. A submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 4, characterized in that: In step S1.2, the heating temperature is 80-100° C. and the heating time is 30-60 minutes.
7. A submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 4, characterized in that: In step S1.3, the heating temperature is 180°C-220°C, and the temperature holding time is 10-24h.
8. The submicron plate-shaped tin phosphide lithium and sodium storage material according to claim 1, characterized in that: In step S2, the inert gas is nitrogen or argon, the sublimation temperature is 370-420°C, and the sublimation time is 1-40h.
9. A battery, which is a lithium ion battery or a sodium ion battery, characterized in that: It uses the submicron plate-shaped tin phosphide lithium and sodium storage material as described in any one of claims 1 to 8 as the negative electrode material.
10. The battery according to claim 9, characterized in that: The preparation method comprises the following steps: (A) weighing submicron plate-shaped tin phosphide lithium storage sodium storage material, acetylene black and sodium alginate, adding a certain amount of distilled water, mixing evenly, grinding and stirring into a paste, and applying it on a copper foil; (B) Drying, slicing, assembling and pressing the coated copper foil to obtain the lithium ion battery or sodium ion battery.
Citation Information
Patent Citations
Preparation method and application of negative electrode material of tin phosphide sodium ion battery
CN106450306A
Tin-phosphide composite material and preparation method and application thereof
CN110034283A
Preparation method of purple phosphorus nanobelt material
CN115010103A
Phosphorus-carbon cathode material based on red phosphorus and preparation method thereof
US20240258523A1
